UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI PECAHAN SEDERHANA MELALUI MEDIA KARTU PECAHAN DI KELAS VI SD NEGERI 011 DESA BARU KECAMATAN SIAK HULU - Maimun Maimun (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The background of this study is the low mathematics learning outcomes of class VI students at SD Negeri 011 Desa Baru, to overcome this problem a classroom action research was conducted by applying fraction card media. This research was conducted in SD Negeri 011 Desa Baru, the subject of this study was class VI students with a total of 24 students. The results of this study show that mathematics learning outcomes have increased in pre-cycle average value obtained is 59.8, in the first cycle obtained an average value of 68.3. And in the second cycle obtained an average value of 82.9. Based on the results of this study, it can be concluded that the mathematics learning outcomes in simple fraction material increase after the fraction card media are applied.